Innovative Freight Bogie NP-X (Current Problems in Rail Vehicles, 2025)
This article deals with the project of an innovative freight bogie. The bogie has standard gauge and is intended for maximum axle load 22.5 tons. The bogie family called NP-X is interchangeable with standard freight bogie Y25. Design of the bogie considers use of rubber springs, swing arms and other innovative elements. Aim of the project is to reflect actual and future requirements for freight bogies. The paper describes actual state of art and the outlook for next years of the grant project.
Keywords: railway vehicles; freight transport; bogie; Y25; NP-X; test rig